Patient perspectives on treatment-related toxicities and therapeutic drug monitoring with tyrosine kinase inhibitors for the treatment of non-small-cell lung cancer - Judith Gulikers; Jeroen Bruinsma; Janna Schoenmaekers; Safiye Dursun; Vivianne Tjan-Heijnen; Robin van Geel; Sander Croes; Lizza Hendriks (Therapeutic Advances in Medical Oncology)
Background: Tyrosine kinase inhibitors (TKIs) have significantly improved treatment-related outcomes of patients with oncogene-driven non-small-cell lung cancer (NSCLC). TKIs are usually well tolerated and used for a prolonged time, although experienced toxicity varies between patients. It is unclear whether patients report all (low grade) toxicities and how these impact their daily lives. The use of therapeutic drug monitoring (TDM) to, for example, manage toxicities is increasingly applied, but there is limited insight into the patient perspective regarding TDM. This qualitative study aims to explore patient perspectives on TKI toxicity and TDM. Methods: Five semi-structured focus group interviews were held, each with three to four patients with NSCLC using a TKI and their (care) partners. Two researchers independently performed a directive content analysis. Results: In total, 16 patients and 12 (care) partners participated. Experienced treatment-related toxicities were encountered limitedly and patients felt no boundaries discussing these with their treatment team. However, symptoms were sometimes not reported as they were doubted as treatment related. The concept of TDM-guided dosing to, for example, reduce TKI exposure to account for dosing outside the therapeutic window resulted in feelings of uncertainty regarding treatment efficacy. Patients emphasized the need for thorough research and frequent check-ups to ensure treatment efficacy. Conclusion: Perceived TKI-related toxicities seem limited, although the treatment team should pay attention to symptoms not directly described by patients as treatment related. In general, patients are open to implement TDM-guided dosing, but only if thorough scientific evidence demonstrates retained or enhanced safety and efficacy.